Recent developments in enzyme promiscuity for carbon–carbon bond-forming reactions. (April 2015) - Miao, Yufeng; Rahimi, Mehran; Geertsema, Edzard M; Poelarends, Gerrit J
Highlights: Many enzymes catalyze reactions other than their biologically relevant one. Catalytic promiscuity has great promise as a source of synthetically useful transformations. Recent advances in enzyme promiscuity for CC bond-forming reactions are discussed. Enzyme promiscuity for Aldol, Michael-type, Mannich, Henry and Knoevenagel reactions has been identified. Abstract : Numerous enzymes have been found to catalyze additional and completely different types of reactions relative to the natural activity they evolved for. This phenomenon, called catalytic promiscuity, has proven to be a fruitful guide for the development of novel biocatalysts for organic synthesis purposes. As such, enzymes have been identified with promiscuous catalytic activity for, one or more, eminent types of carbon–carbon bond-forming reactions like aldol couplings, Michael(-type) additions, Mannich reactions, Henry reactions, and Knoevenagel condensations. This review focuses on enzymes that promiscuously catalyze these reaction types and exhibit high enantioselectivities (in case chiral products are obtained).